Analisis Sistem Hukum Waris Adat Toraja Bagi Anak Angkat dan Anak Kandung - Aulia Rahmah Dwiyanti; Zenita Delia Reviska; Salzabilla Cinta Aurellya (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Every human being will experience death, and will leave his property to his heirs. Indonesia adheres to three inheritance law systems, namely Islamic inheritance law, customary inheritance law, and western inheritance law (Burgerlijk Watboek). Customary inheritance law is a hereditary belief that regulates the distribution of wealth, both material and immaterial, to heirs. Toraja society adheres to a patrilineal system in its customary inheritance law, where inheritance rights are inherited through the male lineage. The Toraja traditional inheritance system has two main concepts, namely pa'tallang and pa'rinding. Pa'tallang Refers to the process of dividing inherited assets based on sacrifices made by the heirs during the testator's lifetime. The greater the sacrifice made, the greater the inheritance rights obtained. Meanwhile, pa'rinding is related to animal sacrifice during death ceremonies, which is also a determining factor in the distribution of inheritance. The results of the research show that adopted children who are recognized by custom can receive almost the same inheritance as their biological children, especially if the deceased person does not have biological children. In addition, biological children who do not participate in this ceremony may face serious consequences in terms of their inheritance rights, which can lead to reduced rights or even loss of inheritance rights altogether.